Digital marketing communication strategy Diraloka in maintaining the national tradition - Haminingtyas, Ana Yulia; Panuju, Redi; Maella, Nur' Annafi Farni Syam (Universitas Bunda Mulia, 2024)
This study discusses how Diraloka maintains national traditions in the postmodern era using marketing 4.0 strategies (online and offline). Technological developments make overlapping cultures accumulate and sometimes can get rid of each other, as well as various values that are often eroded by the speed of the times. This study aims to know and analyze Diraloka's digital marketing communication strategyin maintaining the national tradition of the modern postal era to build brand awareness. This research uses symbolic interaction theory. The paradigm used is constructivism with a qualitative research approach. The method used is a case study. The subject of research is key informants and informants. Data collectiontechniques use interviews, focus group discussion (FGD), observation, and documentation. The results of this study show that Diraloka's involvement in implementing digital marketing communication strategies by voicing national traditions is positively assessed by the audience or the surrounding community. From Diraloka's engagement rate on Instagram, it can be seen that this brand builds a good relationship with its audience. The story shared by Diraloka is packaged through symbols of art, literature, and literacy, and utilizes AI (Artificial Intelligence) technology for its design. Thus, moving together in maintaining,developing, and voicing national traditions can have an emotional impact. Diraloka can form a civic virtue Marketing Communication Strategy 4.0, Diraloka, Symbolic Interaction, National Tradition,Brand Awareness.called #AliansiPejalan and # KawanDira as a form that supports the common good of Indonesian citizens.